Automated 3D Printing of Pediatric Furosemide Tablets: A Personalized Medicine Approach Using Semi-Solid Extrusion and NIR Monitoring - Shokraneh, Farnaz; Filppula, Anne M.; Tornio, Aleksi; Aruväli, Jaan; Paaver, Urve; Kassamakov, Ivan; Sandler Topelius, Niklas (Elsevier, 2026)
This study presents the development of personalized, immediate-release furosemide tablets for pediatric use using semi-solid extrusion (SSE) 3D printing integrated with compounding system solution (CSS) technology. Dose personalization and real-time quality assurance were implemented using near-infrared (NIR) spectroscopy with partial least squares (PLS) modeling, supported by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and surface characterization via scanning white light interferometry (SWLI).
Furosemide formulations (1% and 2% w/w) were prepared using a gel-based excipient and printed in doses from 2 to 10 mg. The NIR-based PLS model exhibited strong predictive accuracy (R² = 0.91; RMSEC = 3.37%), enabling effective, non-destructive blend uniformity monitoring. All formulations met European Pharmacopoeia requirements for drug content (85.0-115.0%) and content uniformity (AV < 15). Dissolution testing confirmed rapid release profiles, with >85% release for all freshly prepared tablets. After six months, the 2% formulation retained adequate performance (88.5%), while the 1% formulation showed a moderate decline (76.3%).
FTIR and XRD analyses revealed no significant drug-excipient interactions, and the crystalline structure of furosemide remained intact throughout storage. SWLI demonstrated surface morphology variations between formulations, revealing that excipient and surfactant levels influenced microtopography and potentially drug release kinetics.
The integration of SSE 3D printing with spectroscopic and imaging tools offers a robust, reproducible, and patient-centric platform for personalized pediatric drug manufacturing. This approach supports the transition toward automated, non-sterile compounding with real-time control, improved dose precision, and enhanced product quality-addressing long-standing gaps in pediatric pharmaceutical care.